Deciphering the role of mitochondria in human fungal drug resistance - Yuanyuan Ma; Yachun Zhou; Tianyuan Jia; Zilin Zhuang; Peng Xue; Liang Yang (Mycology)
As pathogenic fungi increasingly threaten public health, particularly in immunocompromised populations, understanding the mechanisms behind fungal drug resistance has become critical. This review focuses on the pivotal role of mitochondria in this process. Evidence indicates that mitochondria are essential not only for cellular energy metabolism and responses to oxidative stress but also for significantly influencing the expression and activity of drug efflux pumps, which facilitate the expulsion of antifungal agents. Moreover, the intricate roles of mitochondria in iron homoeostasis and calcium signalling are closely linked to the development of drug resistance in fungi. By elucidating these mechanisms, we can identify potential therapeutic targets and pave the way for more effective strategies to combat resistant fungal infections.